"Let Not the Heart in Sorrow Sin": Considering Kierkegaard's Relation to Nihilistic Humanism as a Matter of Christian versus Pagan Truth. (23rd June 2022) - Callaway, Dallas
Abstract: In what way does Kierkegaard's conception of selfhood and despair address the prospect of nihilistic humanism wherein God, sin, and spirit are conceived as the creations of humankind intended to escape the distress of nihilism and imbue life with meaning? By contrasting Kierkegaard's thought with that of a Straussian‐Feuerbachian amalgam of 'Left Hegelianism', I argue that Kierkegaard's work (i.e., taken more holistically than Anti‐Climacus's writings alone so to make the matter of truth more conspicuous than it is in, of note, The Sickness unto Death ) may indeed be interpreted as addressing nihilistic humanism. Specifically, I argue that the topic of truth proves essential for demarcating Kierkegaardian selfhood (the 'inside viewpoint') from Left Hegelianism (the 'outside viewpoint'). First, I recapitulate Kierkegaard's concepts of self ( Selv ) and despair ( Fortvivlelse ). Second, I present in sequence views from 'outside' and 'inside' of Kierkegaard's authorship. Third, taking Kierkegaard to imply engagement of the viewpoints as necessary, I examine the process of 'prefixture' whereby one prefixes the outside to the inside viewpoint or undertakes the countermovement of prefixing the inside to the outside viewpoint. Finally, I conclude that full integration of the two viewpoints is untenable and underscore truth vis‐à‐vis God as both definitive for deciding between the viewpoints and essential for the way in which Kierkegaard addresses nihilistic humanism as a form of despair.